2015
DOI: 10.1007/s11151-015-9493-9
|View full text |Cite
|
Sign up to set email alerts
|

Are Collaborative Agreements in Innovation Activities Persistent at the Firm Level? Empirical Evidence for the Spanish Case

Abstract: We provide evidence on the dynamics in firms' cooperation behaviour in innovation activities. Our main objective is to analyse if collaborative agreements are persistent at the firm level; and, in such a case, to study what are the main drivers of this phenomenon. We also study to what extent such persistence is different from persistence in R&D, so that the former exists on top of the latter. Finally, we deal with the differentiated persistence pattern of collaboration agreements for different types of partne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 50 publications
(74 reference statements)
0
10
0
Order By: Relevance
“…The model specification is as follows (Badillo & Moreno, ; Frees, ): y*it=αnormali+0.25emnormalXit0.25emnormalβ+εit …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model specification is as follows (Badillo & Moreno, ; Frees, ): y*it=αnormali+0.25emnormalXit0.25emnormalβ+εit …”
Section: Methodsmentioning
confidence: 99%
“…First, we select panel data due their benefits listed in the literature (Hsiao, 1985(Hsiao, , 1986Kelvmarken, 1989;Solon, 1989;Baltagi, 2002;p.5) as controlling for individual heterogeneity or allowing for identification and measurement of effects that are simply not detectable in pure cross-section on pure time-series data, among others. Second, we use a random effects probit model due to its advantages regarding a fixed-effect probit estimation (Hsiao, 2003;Badillo & Moreno, 2016) as overcoming the "incidental parameter problem," being appropriate to random samples from large populations or allowing for the treatment of omitted factors.…”
Section: Methodsmentioning
confidence: 99%
“…Collaboration is a complex phenomenon because firms usually collaborate with a variety of partners [7]. Scholars have typically unpacked it based on partnering entity (e.g., [3,[7][8][9]. We follow this tradition by distinguishing between different types of partners.…”
Section: Literature Review and Development Of Hypothesesmentioning
confidence: 99%
“…We follow this tradition by distinguishing between different types of partners. Similar to [8,9], we consider ties with competitors and universities or Higher Education Institutions (HEIs). Moreover, we distinguish between collaborative partners, customers, and suppliers, in a vertical collaboration.…”
Section: Literature Review and Development Of Hypothesesmentioning
confidence: 99%
“…Ghauri et al (2016) argue that the development of the ability to connect through networks facilitates the development of product innovations. Also, Badillo & Moreno (2016), who analyzed Spanish firms that participated in the Panel Technological Panel between 2002 and 2010, found that firms that persistently collaborated with customers, suppliers, and competitors were better able to develop innovations persistently.…”
Section: The Relationship Between Market Network and Technological Imentioning
confidence: 99%